2020
DOI: 10.3390/ijms21228423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Animal Model Systems for Understanding Salivary Secretory Disorders

Abstract: Salivary secretory disorders are life-disrupting pathologic conditions with a high prevalence, especially in the geriatric population. Both patients and clinicians frequently feel helpless and get frustrated by the currently available therapeutic strategies, which consist mainly of palliative managements. Accordingly, to unravel the underlying mechanisms and to develop effective and curative strategies, several animal models have been developed and introduced. Experimental findings from these models have contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…(*, **, and *** indicate p-values < 0.05, 0.005, and 0.0005, respectively. #, ##, and ### represent p-values < 5 x 10 -7 , 5 x 10 -10 , and 5 x 10 -13 , respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(*, **, and *** indicate p-values < 0.05, 0.005, and 0.0005, respectively. #, ##, and ### represent p-values < 5 x 10 -7 , 5 x 10 -10 , and 5 x 10 -13 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…E) Plot showing protein counts per cell of 10 most abundantly detected proteins in progenitor rich cells of PG relative to SMG (*, ** and *** indicate p-values < 0.05, 0.005 and 0.0005, respectively. #, ## and ### represent p-values < 5 x 10 -7 , 5 x 10 -10 and 5 x 10 -13 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we constructed a rat CS model by Wharton's duct PL via an intraoral approach to evaluate the redox status. Compared to the extraoral duct ligation, previous studies indicated that less glandular atrophy and slight residual secretory activity can be observed in the SMG (Kim et al, 2020; Osailan et al, 2006), possibly because of the non‐irritation of the parasympathetic chorda lingual nerve by the intraoral duct ligation. Additionally, partial duct obstruction such as duct stenosis and sialolith is generally believed to cause CS in patients (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…and slight residual secretory activity can be observed in the SMG (Kim et al, 2020;Osailan et al, 2006), possibly because of the nonirritation of the parasympathetic chorda lingual nerve by the intraoral duct ligation. Additionally, partial duct obstruction such as duct stenosis and sialolith is generally believed to cause CS in patients (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SMG gland is the largest of three major salivary glands in rodents and is relatively more radiosensitive than PG (50,56,57), and therefore precision-radiation induced net loss in saliva may be due to higher loss of SMG function compared to PG or SLG. This is supported by more structural abnormalities in the SMG observed in our histological analysis.…”
Section: Discussionmentioning
confidence: 99%